POTENSI KARAKTERISASI BAKTERI TANAH GAMBUT SAPRIK SEBAGAI SUMBER BELAJAR BIOLOGI - Cahyani, Dwi; Yeni, Laili Fitri; Afandi, Afandi; Faturrahman, Mas Akhbar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2026)
West Kalimantan is one of the provinces with the largest area of peatland in Indonesia. Peat soil with a sapric maturity level is generally known to have high bacterial diversity with tremendous potential for characterization. In addition, the characterization of sapric peat soil bacteria has the potential to be used as a biology learning resource. This research aims to conduct a structured evaluation of the potential of West Kalimantan’s sapric peat soil bacteria characterization as a biology learning resource, specifically in the subtopic on Indonesian biodiversity. This research is qualitative and comprises two stages: interviews with a biology teacher and the analysis of requirements for biology learning resources. Through interviews, it was revealed that the central issue in the subtopic of Indonesian biodiversity is the limitation of adequate learning resources for studying biodiversity at the microbial level. Meanwhile, the analysis of biology learning resource requirements showed that the West Kalimantan’s sapric peat soil bacteria characterization met all six specified requirements, accompanied by the synopsis and scenario for the documentary film as a preliminary design. Therefore, the West Kalimantan’s sapric peat soil bacteria characterization has the potential to serve as a biology learning resource for the subtopic of Indonesian biodiversity, enriching the learning of microbial diversity with local biodiversity.